ANALISIS SOSIAL MEDIA, KUALITAS PRODUK DAN TINGKAT HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK AKAOS NGANJUK - Wijianti, Afriliana (Universitas Nusantara PGRI Kediri, 2022)
The main purpose of this research is to find out purchasing decisions on kanjuk clothes by analyzing and assessing the impact of social media, product quality and prices offered. Quantitative causality is the approach used in this study. Random sampling is a method used to find out public opinion with an unlimited number of populations, so sampling data is used, namely as many as 80 respondents from consumers with social media users such as WhatsApp, Instagram, Facebook, and Shopee who have bought products from Akaos Nganjuk. To get the data, an online questionnaire was conducted to the respondents. Henceforth, SPSS software version 25 is a platform used to test the results of research with multiple linear regression. The requirement for the classical assumption test is the main requirement of the incoming data, so that the percentage of social media, product quality, and product price can be known to the purchasing decision which is tested with a coefficient of determination. After testing, it can be concluded that social media, product quality and price have a positive and significant influence on the buyer's decision to wear clothes. In addition, there is a determination coefficient of 70.3% for social media, the quality of the product and the level of the price offered affect the consumer's decision to buy akaos nganjuk. However, for other variables that affect the consumer's decision to make a purchase on kanjuk shirts of 29.7%, research has not been carried out.